(3JGQjN GHf GdaQGJs - (3GHf GdaQGJ , eMeO Hf YHO GdQMje Hf Ydj Hf eMeO, fGUQ GdOjf GdMfaj,J (B807 (3g` s
(3ChdgG (B:s
(3bGd SYjO Hf GdeSjH QMeg Gddg cGf eMeO Hf CHj MfjaI jJjekG ai MLQ YKeGf Hf YaGa QVi Gddg Yfg s
(3BNQgG (B:s
(3jfJgi GdehLhO efg ai PcQ haGI CejQ GdeDefjf GdMSf Hf Ydi Hf CHj WGdH Hbhdg (B: (3Ceg aGWeI GdRgQGA HfJ QShd Gddg Udi Gddg Ydjg hSde hQVi Yfge hdOJg ai GdfUa ef TgQ QeVGf SfI KdGK ef GdgLQI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jTJed GdeNWhW Ydi MhGOK SfI EMOi hKdGKjf Edi SfI JSY hCQHYjf ddgLQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B200 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B159s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs